Microrna profiling in type 2 diabetic kidney disease patients, clinical association and prediction of putative targets by bioinformatics - Zahari Sham, Siti Yazmin (2021)
Diabetic kidney disease (DKD) is the leading cause of chronic kidney disease. The pathogenesis of DKD is multifactorial and culminates in kidney fibrosis. Despite advancement in current biomarkers and therapies such as sodium-glucose- cotransporter-2-inhibitors, disease progression remains. Thus, there is a need to explore new mediators and mechanisms involved. MicroRNAs (miRNAs), which are small non-coding RNAs, regulate gene expression post-transcriptionally. Previously reported dysregulation of circulating miRNAs suggests their potential pathological roles in DKD. miRNA profiling study has not been done in Malaysia. This study aimed to investigate the differentially expressed miRNAs in serum and urine of type 2 diabetes mellitus (T2DM) patients with and without albuminuria. A total of 45 and 33 patients were included in serum and urine studies, respectively. qRT-PCR analysis was done in 12 serum and 11 urine samples in the discovery cohort and 33 paired serum and urine samples in the validation cohort. Ct value above 35 and 38 were considered as negative expression, in serum and urine, respectively. Data analysis was performed in Qiagen software. Relative quantification of miRNA was derived by 2^-ΔCt method, with miRNA expression normalized to that of SNORD95. Fold change was calculated as the normalized miRNA expression in each test sample divided that of in the control sample. The p value was obtained from independent samples t-test of the replicate 2^-ΔCt values for each gene in the control group and each test group. Comparison studies of the continuous and categorical variables were done using Kruskal-Wallis and Pearson chi-square or Fisher’s Exact test, respectively. Correlation between miRNA relative expression and continuous variables was done using Pearson’s correlation coefficient. The statistical significance was defined as p<0.05. Bioinformatics and in-depth literature review were used to investigate their putative mRNA targets and thereby postulate their roles in DKD pathology. Significant association between the study groups and estimated Glomerular Function Rate (eGFR) (p=0.03), urine protein (p<0.01), the use of oral hypoglycaemic agent (p<0.01 and p=0.02, in serum and urine, respectively) and insulin (p<0.01) was seen in serum and urine studies; and that of total cholesterol levels (p=0.05) and serum creatinine (p=0.03) in serum and urine analysis, respectively. Trends of upregulation of miR-874-3p, miR-101-3p and miR-145-5p in serum, and miR-382-5p in urine, of T2DM patients with macroalbuminuria compared to normoalbuminuria were found. Significant upregulation of miR-874-3p (p=0.04) and miR-101-3p (p=0.01) was seen in validation cohort. Significant negative correlations between eGFR and miR-874-3p (p=0.05), miR-101-3p (p=0.03) and miR-145-5p (p=0.05) and positive correlation between miR-874-3p and age (p=0.03) were shown. The predicted putative mRNA targets of miR-874-3p, miR-101-3p, miR-145-5p and miR-382-5p were most likely involved in cellular senescence, focal adhesion, apoptosis and tubulointerstitial fibrosis pathways, respectively. Upregulation of previously known miR-145-5p, and possibly unique miR-874-3p and miR-101-3p in serum and miR-382-5p in urine of T2DM patients with albuminuria in Malaysian population, were found in this study. Significant correlation between eGFR and miR-874-3p, miR-101-3p and miR-145-5p; and between age and miR-874-3p was seen. Future in vitro experiments are worthy to validate the postulated roles of these miRNAs.